KEPUTUSAN PEMBELIAN MENGGUNAKAN PEMBAYARAN E-MONEY GOPAY - Purbohastuti, Arum wahyuni (Jurnal Bisnis Terapan, 2025)
This research on electronic money aims to determine the factors that influence purchasing decisions. The factors is benefits, convenience and security factors. Of these three factors, which factor has the most influence on purchasing decisions using Gopay. The method used in this study was through a questionnaire distributed to 55 respondents consisting of employees and students of the University of Sultan Ageng Tirtayasa ranging in age from 17 to 50 years. Male respondents were 48.1 percent, while female respondents were 51.9 percent. The analytical tool used in this research is multiple linear regression. The results of the Summery model on SPSS, the amount of adjusted R² is 0.582, 58.2 percent of the variation in purchasing decisions can be explained by variations of the three independent variables, namely the benefit factor, the convenience factor and the safety factor. While the remaining 41.8 percent is explained by other reasons outside the model. The results of this study include the benefits and security factors significantly influence the purchase decision.